Demand forecast and material requirement planning application in small-medium enterprise fashion industry - Putra, Irfan Suharto; Handayati, Yuanita (Journal of Business and Management, 2020)
Inventory management is one aspect which is important in maintaining the smoothness of the production process that will ultimately affect the smoothness of consumer demand fulfilment. Companies need to acknowledge the upcoming demand that they can expect to happen. The way to know this is to conduct demand forecasting. Korina is a fashion industry company which actively compete in the industry, particularly in Hijab fashion market. With the ongoing competition between hijab fashion companies, Korina faces the problem of the inability to fulfil the demand, particularly in their dress products. This problem can be traced because Korina does not conduct any demand forecasting and material requirement planning. The objectives of this research are to analyze the demand forecast recommendation of dress products based on the previous data obtained in Korina; to implement the proper material requirement planning basedon the demand forecast in Korina, and; to acknowledge the economic benefit Korina would gain in the future if it follows the material requirement planning and demand forecasting calculated. The methodology used in this research is quantitative approach by calculating Time Series Analysis Demand Forecasting and Economic Order Quantity Material Resource Planning. The result of this research shows that with implementing the appropriate demand forecasting andmaterial requirement planning, Korina is able to achieve economic benefit and fulfil the upcoming demands.Â Keywords: Demand Forecasting, Material Requirement Planning, Fashion Industry, Inventory ManagementÂ Inventory management is one aspect which is important in maintaining the smoothness of the production process that will ultimately affect the smoothness of consumer demand fulfilment. Companies need to acknowledge the upcoming demand that they can expect to happen. The way to know this is to conduct demand forecasting. Korina is a fashion industry company which actively compete in the industry, particularly in Hijab fashion market. With the ongoing competition between hijab fashion companies, Korina faces the problem of the inability to fulfil the demand, particularly in their dress products. This problem can be traced because Korina does not conduct any demand forecasting and material requirement planning. The objectives of this research are to analyze the demand forecast recommendation of dress products based on the previous data obtained in Korina; to implement the proper material requirement planning based on the demand forecast in Korina, and; to acknowledge the economic benefit Korina would gain in the future if it follows the material requirement planning and demand forecasting calculated. The methodology used in this research is quantitative approach by calculating Time Series Analysis Demand Forecasting and Economic Order Quantity Material Resource Planning. The result of this research shows that with implementing the appropriate demand forecasting and material requirement planning, Korina is able to achieve economic benefit and fulfil the upcoming demands. Keywords: Demand Forecasting, Material Requirement Planning, Fashion Industry, Inventory Management